The Exploration of Design Driven Innovation as a Dynamic Capability - Kembaren, Philips; Simatupang, Togar M; Larso, Dwi (The Asian Journal of Technology Management (AJTM), 2011)
Innovation enables companies to attain consistent organic growth that brings benefits to stakeholders. Designthinking approach in innovation has been emergent to be an alternative to technological development path inorder to generate competitive and successful product or service in the market place. Design driven innovationcombines functional and semantic dimensions of products or services in the marketplace. Previous researchhas recently revealed practices of design driven innovation in various industries. However, little is known tothe extent that companies in Indonesia practicing design driven innovation. A theoretical framework withperspective from dynamic capability theoretical lens and guided by Dubin’s theory building methodology isproposed to explain the constructs and role of design in the process of innovation. The research is expected tocontribute a new construct to the existing framework, namely construct that related to how we could assessthe value of the design-driven innovation output, perceived by the costumers.Keywords: design driven innovation, dynamic capabilities, theory building